Menentukan Pola Hubungan Penyebab Kecelakaan Lalu Lintas Dengan Algoritma Apriori - Endang Utari; Paska Marto Hasugian (Jurnal Ilmu Komputer dan Sistem Informasi (JIKOMSI), 2020)
Traffic accidents are one to the leading causes of death. Many factors cause traffic accidents. The high number of accidents that accur is a importtant reason for the Traffic Unit, one of which is the Police, to find out the realitionship between the factors that cause acciden. For this reason, the study that needs to be done is to analyze the existing traffic accident data. The relationship pattern of the cause of accident can be analyzed with an artificial intelligence system namely Data Mining. Based on the above problem, the writer takes the title “Datermining the Relationship Pattern of the Cause of Traffic Accident with the Apriori Algorithm. Based on the above problem, the writer takes the title “Determining the Relationship Pattern of the Cause of Traffic Accident with the Apriori Algorithm. “With the research, it can be used as input to create an ordely intas traffic atmosphere safe and comfortable.